Assessment of Posidonia oceanica traits along a temperature gradient in the Mediterranean Sea shows impacts of marine warming and heat waves - Stipcich, Patrizia; Apostolaki, Eugenia T.; Chartosia, Niki; Efthymiadis, Pavlos Theofilos; Jimenez, Carlos E.; La Manna, Gabriella; Pansini, Arianna; Principato, Elena; Resaikos, Vasilis; Ceccherelli, Giulia (Frontiers in Marine Science, 2022)
Global warming and Marine Heat Waves (MHWs) are having large-scale impacts on the seagrasses and their effects on the Mediterranean endemic Posidonia oceanica need to be properly defined. This research aimed to sharpen the knowledge on P. oceanica response to the warming by correlating the shoot morphology and the productivity of the seagrass to temperature conditions and MHW occurrence. Two correlative studies, along a Mediterranean temperature range (sites at the same latitude), were conducted: one explored the associations of summer 2021 Sea Surface Temperature (SST) and MHWs on P. oceanica morphology and the other used a reconstruction technique (lepidochronological analysis) to relate past temperature conditions and MHW occurrence to proxies of seagrass productivity for the corresponding periods. The results showed that the mean summer temperature affected the P. oceanica leaf necrosis and that MHWs occurrence changed the morphology of the plant by lowering the leaf area and increasing leaf necrosis. Interesting results were also found relating the past thermal environment, since rhizome biomass has been negatively affected by the number of MHWs and rhizome length by the temperature range. This research provides fundamental insights about P. oceanica changes linked to warming and MHWs, identifying the potential plant indicators assisting future experimental and modelling studies. To the best of our knowledge, this is the first time a reconstruction technique is used to evaluate the effects of past MHWs on the morphology and productivity of a plant species.